Kondisi Sistem Informasi Geografis Terhadap Jumlah Ternak Di Kabupaten Pati Tahun 2013 Dan 2014 Berbasis Webgis - Miftakhul Jannah; Bambang Agus Herlambang; Ahmad Khoirul Anam (Lembaga Pengembangan Kinerja Dosen, 2024)
Abstract. Most of the livestock in Pati are still smallholder farms and are not yet large companies. Pati Regency is a support for national beef production, not only for Pati cattle production, but also as a producer of ducklings, chickens and dairy cows. This WEBGIS-based livestock distribution information system in each region was created to support or make it easier for the government and the public to find out developments in the number of livestock products in Pati Regency. There are various sub-districts where livestock output is low due to climatic conditions, feed supply, economic stability for breeders, as well as environmental changes and urbanization. With data on the distribution of livestock products obtained from the Pati Regency BPS data from 2013 and 2014, it is made based on WEBGIS which is able to present distribution information in the form of tables per sub-district and the areas that produce the most livestock. Keywords: Distribution of Livestock Products in Pati Regency, WebGIS).